A comparative study of under-five child mortality in different housing settlements in Soweto, South Africa 2002 - Kutto, Ezekiel Sitienei (My University, 2009)
Background: The study examines the differentials in child mortality existing in the different settlements in Soweto Townships as at May 2002. It attempts to establish the association existing between housing settlement and under-five mortality and as well examine how household characteristics such as building materials, source of drinking water, sanitation facilities and source of energy is associated with under-five mortality. Methods: The research comprises secondary data analysis of a household survey conducted in Soweto in May 2002 by Perinatal HIV Research Unit. The aim of the study is to describe child mortality and explore its relationship to five different housing settlements in Soweto Townships. Kaplan Meier curves were fitted to examine differentials in child mortality in the different housing settlements and Log rank test was used to compare the survival curves. Logistic regression models were fitted to establish factors that were associated with under-five mortality in Soweto Townships as a whole. Results: A total of 2741under-five surviving children and 84 under-five deaths were studied. Informal settlements recorded the highest overall under-five mortality rate (15.9 per 10000 child years) while private sector housing settlement recorded the least (3.3 per 10000 child years) of all the housing settlements. The overall under-five mortality in Soweto Townships was 10.4 per 10000 child years. After controlling for other household characteristics settlement was significantly associated with high under-five mortality (Council settlement OR 3.3, P=0.032, 95 CI; 1.113, 10.24, Informal settlement OR 5.10, P=0.005, 95% CI; 1.633, 15.99 and Hostel settlement OR 4.09, P=0.012, 95% CI; 1.357, 12.35). Use of paraffin and candles were also significantly associated with high under-five mortality (OR 3.4, P-value<0.001, 95% CI; 2.416, 19.15 and OR 7.2 P-value=0.014, 95% CI; 1.25, 8.88 respectively). Conclusions: Private sector housing settlements reported lower under-five mortality rates in Soweto Townships (3.3 per 10,000 child years) and was less associated with high mortality in comparison to the other housing settlements (Informal, council and hostel housing settlements) in Soweto Townships. Use of paraffin and candles for lighting in households were mainly associated with high under-five mortality in Soweto Townships in comparison to those households that used of electricity.
Keywords: child mortality